Analysis of The Formation of Initial Information And Evaluation of A Constructive Solution in Terms of Ergonomic Parameter (Conference Zone, 2022)
Modern flow of information has led to the problem of "big data". This required the creation of special technologies for fast processing of these data. The need for automated data mining became clear primarily because of the historical huge arrays of queues and newly collected data. It is difficult to estimate the daily volume even roughly, intellectual analysis of the data collected by various companies, government, scientific and medical organizations. The human mind, even an educated analysis such as a professional mind, could not in time be able to analyze such large streams of information.As a basis for the modern intellectual analysis of organizations, it is based on certain templates that reflect the fragments of interactions in the data.